The Story of the Self in the Aftermath of Crisis: A Case Study. Issue 1 (2nd January 2016) - Grimell, Jan
Abstract : Adopting a dialogical framework, a case study is presented that explores the story of the self in the aftermath of crisis. An analysis and interpretation of the case study leads to the hypothesis that integration and dialogue through promoters, coalitions, and cooperation are needed in the process of reconstructing the story and the self. A cultural narrative may facilitate such a process. It is proposed that during these developments a new core position may arise that has the capacity to unite and reconcile the self while promoting growth in the aftermath of crisis. Future research is encouraged that examines this hypothesis more broadly.